(untitled) (Stato, Chiese e pluralismo confessionale, 2022)
Riflessioni sul “giusto processo” in diritto canonico, sullo sfondo del riequilibrio in corso fra diritti e poteri nella Chiesa cattolica * Reflections on due process in canon law, against the background of the ongoing rebalancing of rights and powers in the Catholic Church * SOMMARIO: 1. Tra ‘agàpe’ e storia. Una premessa neotestamentaria - 2. (segue) Potere giudiziario e sovranità binaria. Il diritto divino dei vescovi - 3. “Heri dicebamus”? Sul tentativo curiale di ridurre il Vaticano II a mero evento culturale - 4. Origini e sviluppo dell’opposizione anticonciliare: il terreno del processo - 5. La prima controriforma vaticana: la “Nova agendi ratio in doctrinarum examine” - 6. Resilienze (non sopprimibili) di una costituzione materiale parallela? - 7. Persistenze storico-culturali di fatti compiuti prevaricanti e diritto di resistenza - 8. (segue): a) Su un “golpe Gasparri” in danno di due diversi progetti di giustizia amministrativa - 9. b) … e sulla “falsa” giustizia amministrativa del card. Grocholewski (e suoi) - 10. c) Lo sconcerto della scoperta nel clero di pratiche corruttive su minori - 11. (segue) … e l’abnorme deriva inquisitoria dei processi de delictis gravioribus - 12. Sulla voluta inattuazione dei tribunali amministrativi interdiocesani - 13. Sulle odierne, inedite sperimentazioni in tema di contenzioso matrimoniale - 14. Tra rescritti di giustizia e giurisdizione inter partes: un sottaciuto tema fondamentale - 15. Dalla frammentazione (relitto amaro di incertezze strategiche) a un ritorno al Lateranense IV? ABSTRACT: The essay notes a continuity, starting with the Tridentine, in the deviation from the fundamental principles of what we today call ’due process’, imposed by Innocent III since the Council Lateran IV. The progressive spread of special jurisdictions seemed to express the degradation of certain principles and values of medieval common law, from which canon law was gradually moving away. The 1917 code is to be seen as the final sanction and ratification of that involutional process. The author then examines the 1983 reform, which moved between reforming timidity and curial overbearingness: the special jurisdictions were untouchable; the planned chapter on administrative tribunals was deleted in extremis. The impression is that no serious follow-up has been given to the reforms ordered by Paul VI in fulfilment of the Council mandate, starting with the Doctrinal Dicastery. In fact, the centralist innovation as codified in 1917 substantially persists. It is to this petrified block, rebuilt under the two pontificates following Pope Montini, that Pope Francis I attempts to react with innovative ideas that however appear technically imprecise, and in many ways inadequate to the actual dimensions of the Holy See’s overall non-fulfilment of the conciliar mandate. Against the backdrop of these perhaps promising innovative signs, Pope Francis appears on the other hand invariably opposed by the Curia, both in the field of substantive and procedural law.